(untitled) (International Journal of Engineering and Computer Science, 2015)
Mobile Adhoc Networks (MANETS) allows portable devices to establish a communication independent of a central infrastructure. The wireless links in this network are highly error prone and can go down frequently due to mobility of nodes.MANETS are vulnerable to many security attacks because of shared channel, insecure operating environment, lack of central authority, limited resource availability, dynamically changing network topology and resource constraints. Among the different attacks at the different network layers the wormhole attack is the most malicious. In this work, the wormhole attack is implemented in three different modes i.e. all pass, all drop and threshold mode with varying network sizes. Due to a highly dynamic environment routing in MANETS is a critical task. To make the network reliable we need efficient routing protocols. The routing protocols are of three kinds i.e. Proactive, reactive and hybrid. Four proactive protocols(DSDV, OLSR ,WRP,GSR,TBRPF) are analyzed in the presence of the worm hole attack considering four parameters which are throughput, average end-to-end delay, average jitter and packet delivery ratio in mobility and non-mobility domain.